2014
DOI: 10.1089/jamp.2013.1075
|View full text |Cite
|
Sign up to set email alerts
|

PediatricIn VitroandIn SilicoModels of Deposition via Oral and Nasal Inhalation

Abstract: Respiratory tract deposition models provide a useful method for optimizing the design and administration of inhaled pharmaceutical aerosols, and can be useful for estimating exposure risks to inhaled particulate matter. As aerosol must first pass through the extrathoracic region prior to reaching the lungs, deposition in this region plays an important role in both cases. Compared to adults, much less extrathoracic deposition data are available with pediatric subjects. Recently, progress in magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 166 publications
0
12
0
1
Order By: Relevance
“…Several correlations exist in the literature that use a variety of parameters to characterize variability, including SA/V or V/SA (Carrigy et al, 2014; Garcia, et al, 2009; Golshahi, et al, 2011; Storey-Bishoff, et al, 2008). Results showed that for control conditions without and with condensational size change considered, the nasal cavity DE correlated very strongly with SA/V (R = 0.993, p < 0.007 and R = 0.991, p < 0.01), but for EEG conditions the two parameters were not related.…”
Section: Discussionmentioning
confidence: 99%
“…Several correlations exist in the literature that use a variety of parameters to characterize variability, including SA/V or V/SA (Carrigy et al, 2014; Garcia, et al, 2009; Golshahi, et al, 2011; Storey-Bishoff, et al, 2008). Results showed that for control conditions without and with condensational size change considered, the nasal cavity DE correlated very strongly with SA/V (R = 0.993, p < 0.007 and R = 0.991, p < 0.01), but for EEG conditions the two parameters were not related.…”
Section: Discussionmentioning
confidence: 99%
“…(61) Numerous in vitro studies have focused on intersubject variability due to airway morphology (in adults and children) and inspiratory flow rate. (58,(62)(63)(64)(65) Simulation of realistic patient inhalation maneuvers during in vitro testing, potentially including simulation of mis-use, (66) can also be important in establishing in vivo-in vitro correlations, in particular for DPIs where emitted doses and aerosol size distributions are flow-rate dependent. (20,67,68) Results of in vitro experiments have also been used to validate models or to derive analytical correlations that can be used in lieu of deposition models, especially for extrathoracic deposition.…”
Section: Fig 2 Coronal Slices Of 3d Single Photon Emissionmentioning
confidence: 99%
“…(20,67,68) Results of in vitro experiments have also been used to validate models or to derive analytical correlations that can be used in lieu of deposition models, especially for extrathoracic deposition. (62,63,65,69) Such correlations must be applied with caution in predicting ADD or total aerosol deposition from single-breath inhalers, as discussed above in the previous section.…”
Section: Fig 2 Coronal Slices Of 3d Single Photon Emissionmentioning
confidence: 99%
“…Le matériau de nature antistatique de ces chambres d'inhalation peut certainement faciliter la déli-vrance de la fluticasone. D'autre part, la respiration nasale exclusive, qui certes mime la façon d'inhaler d'un jeune enfant, et qui est connue pour diminuer la quantité de particules inhalables délivrée [11,12], peut peut-être aussi induire un mouvement plus limité des valves inspiratoire et expiratoire de certaines chambres d'inhalation et donc diminuer la prise médicamenteuse quantifiée au cours de cette étude. Enfin, les écart-types importants constatés lors des mesures de dépôt trachéal, alors que les expériences ont été réalisées dans des conditions in vitro extrême-ment favorables à la reproductibilité du dépôt trachéal, sont sûrement liés à des différences d'étanchéité au niveau l'interface masque-visage entre chaque expérience pour une même chambre d'inhalation.…”
Section: Discussionunclassified